2008
DOI: 10.1128/jb.01671-07
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic and Biochemical Evidence for the Identification of the Type III Secretion System Needle Protein ofChlamydia trachomatis

Abstract: Chlamydia spp. express a functional type III secretion system (T3SS) necessary for pathogenesis and intracellular growth. However, certain essential components of the secretion apparatus have diverged to such a degree as to preclude their identification by standard homology searches of primary protein sequences. One example is the needle subunit protein. Electron micrographs indicate that chlamydiae possess needle filaments, and yet database searches fail to identify a SctF homologue. We used a bioinformatics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 67 publications
1
65
0
2
Order By: Relevance
“…It is possible that CopB is diffusible in the inclusion membrane and could enable translocation in trans instead of mediating flow of effectors in a contiguous process from bacterium to host. A contiguous, rim-like staining pattern is apparent for CopB by 18 to 20 h postinfection (15), and this is in contrast to a more punctate distribution typical of the needle protein CdsF (8). Moreover, Akopyan, et al, recently demonstrated that Yersinia and Salmonella effector proteins could be translocated via an intermediate step from the bacterial exterior (2).…”
Section: Discussionmentioning
confidence: 89%
“…It is possible that CopB is diffusible in the inclusion membrane and could enable translocation in trans instead of mediating flow of effectors in a contiguous process from bacterium to host. A contiguous, rim-like staining pattern is apparent for CopB by 18 to 20 h postinfection (15), and this is in contrast to a more punctate distribution typical of the needle protein CdsF (8). Moreover, Akopyan, et al, recently demonstrated that Yersinia and Salmonella effector proteins could be translocated via an intermediate step from the bacterial exterior (2).…”
Section: Discussionmentioning
confidence: 89%
“…The structure of this translocon and the nature of its interaction with the host membrane remain unknown, as it is never co-isolated with the detergent-solubilised core T3SS complex. Chlamydiae encode homologues of core complex components [15,16,17], yet in comparison to other pathogens in which the genes encoding T3SSs are grouped together on pathogenicity islands, T3SS-related genes are distributed across the genome in four distinct clusters composed of at least ten separate operons [18]. Unusually, Chlamydiae also possess two copies of putative translocon components (CT578/CT579 and CT860/CT861) identified by primary sequence similarity to the Yersinia YopB and YopD translocon proteins [19], although the significance of this remains unresolved.…”
Section: The Chlamydial T3ss: the Exception Or The Rule?mentioning
confidence: 99%
“…The structure of this translocon and the nature of its interaction 19 with the host membrane remain unknown, as it is never co-isolated with the 20 detergent-solubilised core T3SS complex. Chlamydiae encode homologues of core 21 complex components [15,16,17] membrane that initially loosely encloses the EB and co-envelopes host material 5 transitions to form a tight structure proximal to the EB surface. During this time, the 6 EBs lose their polarity, with an associated reduction of the pronounced periplasmic 7 widening and a decrease in assembled T3SSs (Figure 2) [26].…”
mentioning
confidence: 99%
“…Most of our current knowledge of the structure of the chlamydial type III secretion apparatus comes from the discovery of in vitro protein-protein interactions between chlamydial type III components. [27,[32][33][34][35][36][37][38][39][40][41], while the detection of new chlamydial effectors has involved expression and secretion of recombinant chlamydial proteins in heterologous type III secretion systems of other bacteria [3 8, 40-43]. The predicted structure of the Chlamydia type III secretion apparatus and its components is visualized in Figure 1.…”
Section: Type III Secretionmentioning
confidence: 99%
“…Such structural conservation has allowed for the quick identification of putative chlamydial type III secretion proteins in silica analysis based on conserved structural and genetic domains [25][26][27][28][29][30][31]. Many groups have identified putative Chlamydia TTSS components by these approaches, but because of Chlamydia species' genetic intractability, it has remained a challenge to confirm the function of these proteins.…”
Section: Type III Secretionmentioning
confidence: 99%